Investigation of Taguchi optimization, equilibrium isotherms, and kinetic modeling for phosphorus adsorption onto natural zeolite of clinoptilolite type - Bahareh Razmi; Reza Ghasemi-Fasaei (Adsorption Science & Technology)
Adsorption process plays an important role in the removal of phosphorus from aqueous solutions. A laboratory experiment was conducted to investigate the adsorption characteristics of phosphorus onto natural zeolite and to find out the relative importance of some controllable treatments in phosphorus adsorption process using the Taguchi optimization methodology. Results showed that the adsorption of phosphorus in the presence of Fe 3+ and Al 3+ was higher than that in the absence of these two cations probably due to the adsorption of phosphorus-bearing anions on opposite charges of these cations. Also, increase in contact time tended phosphorus adsorption to be increased. The addition of base and acid treatments caused an increase and a decrease, respectively, on phosphorus adsorption. The order of effectiveness of treatments on the values of phosphorus adsorption was as follows: acid/base treatment >sorbent to sorbate ratio > modification with aluminium (Al)/iron (Fe) >contact time >phosphorus concentration. Phosphorus adsorption data well fitted to the Freundlich isotherm model. The pseudo-second order was the best model describing phosphorus adsorption kinetics. According to the results reported herein, it is assumed that the main mechanism controlling phosphorus adsorption onto natural zeolite is chemisorption.